Convective heat transfer and fluid flow study over a step using nanofluids: A review - Mohammed H.A. (2023)
Research in convective heat transfer on internal separated flows has been extensively conducted in the past decades. This review summarizes numerous researches on two topics. The first section focuses on studying the fluid flow and heat transfer behavior of different types of single-phase fluid flows over backward facing step (BFS) at different orientations. The second section concentrates on everything related to nanofluids; its preparation, properties, behavior, applications, and many others. The purpose of this article is to get a clear view and detailed summary of the influence of several parameters such as the geometrical specifications, boundary conditions, type of fluids, and inclination angle on the hydrodynamic and thermal characteristics using (BFS). The reattachment length and maximum Nusselt number are the main target of such research where correlation equations were developed and reported in experimental and numerical studies. The heat transfer enhancement of nanofluids along with the nanofluids preparation technique, types and shapes of nanoparticles, base fluids and additives, transport mechanisms, and stability of the suspension are also discussed. 2011 Elsevier Ltd. All rights reserved.